A recurrent neural network approach for multiple-aspect trajectory classification via space, time, and semantic embeddings - Petry, Lucas May (2020)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência da Computação, Florianópolis, 2020.